2012
DOI: 10.1111/hex.12003
|View full text |Cite
|
Sign up to set email alerts
|

Customer interest in and experience with various types of pharmacy counselling – a qualitative study

Abstract: Background Despite pharmacists' extensive knowledge in the optimization of patients' medical treatments, community pharmacies are still fighting to earn patients' trust with respect to medicinal counselling at the counter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…85 Involving pharmacy staff in an intervention that involved identifying product misuse led to raising awareness amongst them and made them realize their vital role they had in supporting patients to use medicine safely. 68…”
Section: Attributes Of Community Pharmacy Where Npms Are Suppliedmentioning
confidence: 99%
“…85 Involving pharmacy staff in an intervention that involved identifying product misuse led to raising awareness amongst them and made them realize their vital role they had in supporting patients to use medicine safely. 68…”
Section: Attributes Of Community Pharmacy Where Npms Are Suppliedmentioning
confidence: 99%
“…A survey of primary care physicians reported little recognition of a role for pharmacists in the delivery of PGx testing [8]. Attitudes about pharmacist counseling are reported to be variable, due in part to the uncertain role of pharmacists and customer expectations [97]. Additionally, it is difficult to generalize patient and practitioner perspectives based on current literature as data are derived from various countries, which have different training and practice for pharmacists.…”
Section: Introductionmentioning
confidence: 99%
“…This population understands the terminology used (d ¼ 0.34), they are told how to take the medicine they receive (d ¼ 0.61) and they know who to ask if they have questions regarding medicines (d ¼ 0.38). Kaae, Traulsen, and Nørgaard (2012) interviewed customers at retail pharmacies in Denmark and found that only 42.9% of them expected to be questioned when purchasing medicine. In Nigeria (Oparah & Kikanme, 2006), consumers were satisfied with their pharmacists' professional and counselling service but not satisfied with the provision of the other services in community pharmacy.…”
Section: Discussionmentioning
confidence: 99%